LOCAL GOVERNMENT INTERVENTION ON STREET LEVEL BUREAUCRACY OF BASIC HEALTH PROVISION IN DECENTRALIZED ERA - Arief Priyo Nugroho (Pusbindiklat - LIPI, 2012)
In health care provision, puskesmas (Community Health Center) can be described as street level bureaucracythat has important role in improving health services. The study aimed to analyze political intervetion inhealth service provision. This study used Michael Lipsky theory about street level bureaucracy and Karl Marxtheory about class and state to analyze pattern of intervention. This case study research was conducted in SouthKrembangan, Surabaya. Observation and secondary data analysis are the main tools to trace the pattern of localgovernment intervention in primary health care at puskesmas. The result shows that local government has beenbeing admitted indirect intervention in health service provision. The intervention was proved by the puskesmastreatment that referred to implement curative program from promotive and preventive that was actually its dutyand main function.